Discourses in interaction - Tanskanen, Sanna-Kaisa. (Amsterdam ; Philadelphia : John Benjamins Pub. Co., 2010)
The fourteen contributions in this collection come from different approaches in pragmatics, interactional linguistics, conversation analysis, discourse analysis and dialogue analysis; the name given to what is studied ranges from spoken language and conversation to interaction, dialogue, discourse and communication. What the articles have in common is a similar starting point: they are informed by a form of linguistic understanding which has emerged within what could be called the interactional turn. The materials investigated come from several different languages, representing a variety of in.
Discourses in Interaction; Editorial page; Title page; LCC data; Table of contents; Acknowledgments; Discourse and the interactional turn; Part 1. Dialogues between contexts; Contexts in context; Communicative activity types as organisations in discourses and discourses in organisations; Discourse and context in a historical perspective; Part 2. Constructing identity across genres; Pronominal choice in French conversational interaction; Constructing interpersonal relations in the discourse of Russian media; Who communicates in the media supported by the Russian Church?
Includes bibliographical references and index.
Print version record.
English.
eBooks on EBSCOhost
Keywords: Discourse analysis; LANGUAGE ARTS & DISCIPLINES -- Vocabulary; Discourse analysis; Diskursanalyse; Interaktion; Pragmatiek; Discourse analysis; Verbale communicatie; Konversationsanalyse; Interaktion; Discourse analysis; Diskursanalys; Electronic book